2011
DOI: 10.1007/s00421-011-2088-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical power in adolescents: physiological bases and assessment using all-out exercise

Abstract: This study examined whether critical power (CP) in adolescents: (1) provides a landmark for maximal steady-state exercise; and (2) can be determined using 'all-out' exercise. Nine active 14-15 year olds (6 females, 3 males) performed five cycling tests: (1) a ramp test to determine VO(2peak); (2) up to four constant power output tests to determine CP; (3-4) constant power output exercise 10% above and 10% below CP; and (5) a 3 min all-out cycle test to establish the end power (EP) at 90 and 180 s of exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Williams et al [6] reported non steady-state responses in O2 and blood lactate during cycling at CP and 10% above CP and concluded, that CP does not represent a sustainable exercise intensity in adolescents. In accordance, Barker et al [10] showed increases in O2 and blood lactate over time, accompanied by reduced time to exhaustion during cycling 10% above CP. At an intensity 10% below CP, all participants completed 30 min of exercise and a steady-state in O2 and blood lactate profile was identified [10].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Williams et al [6] reported non steady-state responses in O2 and blood lactate during cycling at CP and 10% above CP and concluded, that CP does not represent a sustainable exercise intensity in adolescents. In accordance, Barker et al [10] showed increases in O2 and blood lactate over time, accompanied by reduced time to exhaustion during cycling 10% above CP. At an intensity 10% below CP, all participants completed 30 min of exercise and a steady-state in O2 and blood lactate profile was identified [10].…”
Section: Introductionsupporting
confidence: 70%
“…In accordance, Barker et al [10] showed increases in O2 and blood lactate over time, accompanied by reduced time to exhaustion during cycling 10% above CP. At an intensity 10% below CP, all participants completed 30 min of exercise and a steady-state in O2 and blood lactate profile was identified [10].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Whereas in adults all work rates in the severe exercise intensity domain may elicit VO 2 max when exercise is continued to fatigue (30)(31)(32), this may not be the case for children (5,6,48). However, we reasoned that this procedure would permit identification of VO 2 max thereby making the issue of secondary criteria redundant.…”
mentioning
confidence: 99%
“…44 In adults, at exercise intensities above the MLSS or CP the slow component of p _ VO 2 rises rapidly over time and eventually reaches peak _ VO 2 but this phenomenon has not been observed in children. 37,45 The mechanisms underlying the p _ VO 2 slow component remain speculative but it has been established that w86% have been accounted for at the contracting muscles. 46 During exercise above the T LAC the p _ VO 2 slow component is associated with a progressive recruitment of additional type II muscle fibres with the low efficiency contributing to the increased oxygen cost of exercise.…”
Section: Pulmonary Oxygen Uptake Kineticsmentioning
confidence: 99%